Faktor-faktor yang mempengaruhi permintaan barang online melalui shopee paylater sebagai variabel intervening (Studi kasus pada mahasiswa Universitas Jambi) - Dwi Lestari, Winda; Zulfanetti, Zulfanetti; Heriberta, Heriberta (e-Journal Perdagangan Industri dan Moneter, 2024)
This study aims to: 1) Know the characteristics of students who use shopee paylaters at Jambi University, 2) Know the effect of promotions, prices and allowances on demand through spaylaters directly and indirectly. The research method in this study was descriptive quantitative using a questionnaire data collection method. The population in this study were all students who had used the spaylater payment method at least once and the sample used was 97 students. The data analysis tool used is path analysis with the help of the amos application. The results of the path analysis in this study are that the pocket money variable directly has a significant effect on the spaylater, but not the promotion and price variables. Besides that, the variables of pocket money and spaylater have a significant effect on demand. While indirectly, based on the sobel test, pocket money has a significant effect on demand, while the promotion and price variables have no significant effect on demand.